Implementasi Kebijakan Pembelajaran Daring di Sekolah Olahraga Negeri Sriwijaya Palembang - Handayani, Diana; Sandy, Amiruddin; Saswita, Saswita (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
Implementing online learning is not an easy task in Indonesia. In the implementation process, there are many limitations and problems that occur in the field. This research was carried out at the Sriwijaya State Sports School on the grounds that the school had implemented online learning during the Covid-19 pandemic. However, in practice many problems were found. The goal to be achieved in this research is to find out and describe the implementation of Online Learning for students of the Sriwijaya State Sports School. The type of this research is descriptive with a qualitative approach. Descriptive research presents a description of a situation or social phenomenon in detail. Conclusion, as follows: (1). Implementation of Online Learning Policy at the Sriwijaya State Sports School for the communication dimension of this policy implemented well starting from disseminating information to socializing the policy, however the implementation was limited. (2) Resource dimension, with indicators of human resources, adequate supporting facilities and infrastructures, and for funding resources in accordance to their designation. (3). Disposition dimensions with officers' commitment indicators and coordination with related parties. Implemented in accordance with the commitment of policy implementers and coordinated with related parties. (4) Dimensions of the bureaucratic structure, Requirements for Obtaining Services Service Processes/Procedures, the Online Learning Policy at the Sriwijaya State Sports School is in accordance with existing procedures and rules.